2010
DOI: 10.1002/aqc.1101
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ecological responses to a conservation translocation of powan (Coregonus lavaretus) in Scotland

Abstract: ABSTRACT1. The establishment of refuge populations has become a common management tool for threatened fish species in recent years, yet the effects of translocation are not fully understood in a conservation context.2. This paper examines the hypothesis that phenotypic changes have occurred during the formation of two refuge populations of the nationally rare powan (a freshwater fish species) which were established in Loch Sloy and Carron Valley Reservoir in Scotland.3. Significant differences in head morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…Moreover, captive breeding and reintroduction as conservation tools require many considerations (IUCN, ), and the genetic status of the stocks used in a reintroduction project would need to be evaluated and monitored (Aguirre‐pabón, Barandica, & García, ). Thus, the establishment of refuge populations (Ardestani, Rogelio, Reyes, & Laude, ; Etheridge, Bean, Maitland, & Adams, ) is recommended for the conservation of this freshwater species, and in order to maintain local‐level adaptive potential, the refuge populations, as conservation‐significant units, should be selected carefully (Ardestani et al, ; Hayes, Krahl, Werneke, & Armbruster, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, captive breeding and reintroduction as conservation tools require many considerations (IUCN, ), and the genetic status of the stocks used in a reintroduction project would need to be evaluated and monitored (Aguirre‐pabón, Barandica, & García, ). Thus, the establishment of refuge populations (Ardestani, Rogelio, Reyes, & Laude, ; Etheridge, Bean, Maitland, & Adams, ) is recommended for the conservation of this freshwater species, and in order to maintain local‐level adaptive potential, the refuge populations, as conservation‐significant units, should be selected carefully (Ardestani et al, ; Hayes, Krahl, Werneke, & Armbruster, ).…”
Section: Discussionmentioning
confidence: 99%
“…While this has not been found in these translocated populations to any great extent, no CR fishes were ever identified as a putative C. clupeoides and the proportions of LS and CR fishes classed as unidentifiable were greater than for LL fishes. Etheridge et al (2010 b ) found that after only four generations LS and CR fishes were found to be diverging phenotypically in different directions, presumably due to physical and biotic differences between sites. It is possible that, if this diversion continues, LS and CR fishes might ultimately be classed as different species using phenotypic characters.…”
Section: Discussionmentioning
confidence: 99%
“…Only L F and N EDxSL were significantly different between these sites. A comparison of LL coregonids in comparison to the translocated populations in LS and CR found significant differences in growth rates and in head morphology between populations presumably due to phenotypic plasticity (Etheridge et al, 2010b). It has been suggested that allometric traits may change the diagnosis of a species when moved to a different environment due to the often reported changes in growth in translocated coregonid populations (Svärdson, 1957).…”
Section: A S S E S S M E N T O F P H E N Ot Y P I C T R a I T S I N Cmentioning
confidence: 99%
“…Noting the threats to both species such as habitat loss, over-exploitation and introduction of non-native species (Paller et al, 2011) candidate strategies include the site-specific translocation and establishment of a refuge population as suggested by Etheridge et al (2010). However, to maintain local-level adaptive potential, the selected refuge populations should be obtained from the appropriate geographical range (Davey et al, 2003).…”
Section: Implications For Conservationmentioning
confidence: 99%